Pengembangan Media Proshow Gold Berbasis Buletin Bergambar Pada Materi Ciri Khusus Makhluk Hidup - Choirisijah, Isti (CV. Creative Tugu Pena, 2022)
The purpose of this study is to determine the need, form and effectiveness of the development of a bulletin-based gold bulletin proshow media on the specific characteristics of living things, which is carried out by (a) conducting preliminary research, (b) carrying out planning (defining abilities, formulating objectives, determining goals, determining learning materials and sequences, (c) Develop learning media with proshow gold, (d) Material expert test and media expert test, (e) Small-scale initial and revised field tests, (f) Large-scale and final revision tests, (g) application in learning. This type of research used in this research is Research and Development (R&D). Research and development (R&D) is a research strategy or method. The subjeck in this study were all grade VI students in MI Kedu Subdistrict, Temanggung Regency, which amounted to 12 MI, but researchers only took samples from grade VI students in MI Kutoanyar, amounting to 42 students. The results and objectives of this study are the development of a proshow gold media based on pictorial bulletin The development of proshow gold media on the special characteristics of living things in MI Kutoanyar Kedu is effective. The significance value of tcount = 5.58 with Sig. (2-tailed) 0,000. Before looking at the table of values of t, first must be with db = N - 2. Because the number of samples studied were 40 students, then db = 40 - 2 = 38. The value of db = 38 at a significance level of 5% obtained t-table = 1,99045. Because tcount> ttable or 5.54> 1.99045 and Sig. (2-tailed) = 0,000 <0.05 then H0 is rejected and H1 is accepted. Keywords: Developing Media, Learning Media, Media Proshow Gold